Apakah Attractiveness of Endorser Berpengaruh terhadap Attitude, Social Media Engagement, dan Purchase Intention? - Ridho, Muhammad Rasyid; Fitriana, Ana; Listiana, Erna; Ahmadi, Ahmadi (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
Rucas's marketing strategy leverages online promotions and creative content to reach a wider audience. The unique approach in advertising, featuring unconventional models, successfully attracted the attention of social media users. By considering customer perceptions of advertisements and brands as mediating variables, the influence of endorser attractiveness on customer purchase intentions is the objective of this research. Purposive sampling was used to select 153 people who are familiar with the Rucas advertisement. The data collected through online questionnaires were analyzed using Structural Equation Modeling (SEM). Menurut hasil penelitian, daya tarik selebriti memiliki dampak signifikan terhadap sikap terhadap iklan dan merek. Except through the mediation of attitudes and engagement on social media, that attractiveness does not directly influence purchase intentions. These results indicate that, to enhance advertising effectiveness and drive purchase decisions, marketing strategies involving endorsers must consider the role of attitude and engagement mediation.